"Constructed Wetland Park as Happy Public Space to Achieve Quality of life: Case Study of 10 Ramadan City". Issue 1 (1st February 2022) - Barmelgy, M EL; Elsaman, S M; Refaat, D T; Haron, A; El Maalt, A E
Abstract: Happy public park (HPS) spaces can be defined as a place that gives us a positive perception that motivates us to spend time and live an unforgettable experience in our memory. As important as the urban blue-green spaces, constructed wetland parks (CWPs) have a spread of environmental and social benefits. Constructed wetlands now are used as an environmental contrivance in many countries. It achieves many benefits like increasing biodiversity, habitats, water treatment, and decreasing pollution. In the last decade, this technology was used in Egypt as a tool for water treatment-funded projects like Manzla lakes and small-scale projects. The research aim is to identify and define the relation between a happy public space (HPS) and a constructed wetland park (CWP) and evaluate the indicators which can create a constructed wetland park (CWP) as a happy public space (HPS), The simulated data collected from an experts' point of view. The method is to link the indicators that affect the public space especially in a Case study on the 10th of Ramadan "constructed wetland park" to be happy public space and analyzing (WTP) and (HPS) indicators through interviews, workshops, and questionnaires as were statistical analysis of the linkages between the indicators to measure the effective indicators and removing ineffective indicators, to reach a guideline which can create a happy public space in constructed wetland park.